Redesign Website Mitra10 Untuk Meningkatkan Kepuasan Pelanggan - Yulianto P, Dika; Naufal E, Audwi; Wildan H, Muhammad; Rizky M, Faizal; Dafino H, Muhammad (Jurnal Etnik: Ekonomi-Teknik, 2023)
UI/UX (User Interface/User Experience) are critical elements in digital design that influence user interactions. This article discusses the importance of UI/UX in general and focuses on the redesign of the Mitra10 website. The research aims to enhance user experience, navigability, and engagement through responsive and intuitive design changes. The research method involves user analysis, competitor studies, and data-driven design implementation. Results include a cleaner interface, clear icons, and improved navigation. This redesign is expected to enhance user efficiency and strengthen the Mitra10 brand image.